A revision of the Australian species of Howickia Richards (Diptera: Sphaeroceridae: Limosininae) - Kuwahara, Gregory K.; Marshall, Stephen A. (Zootaxa, 2022)
Howickia Richards, 1951, the largest genus of Sphaeroceridae in Australia, is revised to include 43 species, including all wingless Australian species of the family. The following new species are described: H. acicula (TAS), H. auricoma (VIC), H. biantenna (TAS), H. cruspica (VIC), H. erythrocephala (NSW), H. flagella (TAS), H. grandisterna (TAS), H. holti (NSW), H. irwini (NSW), H. loligo (TAS), H. notechis (TAS), H. nuda (NSW), H. pertusa (TAS), H. pinnula (TAS), H. pseudovittata (NSW, QLD), H. robustaseta (NSW), H. tricolor (NSW), H. truemani (TAS), H. wamini (NSW, QLD, TAS, WA), and H. xanthocephala (QLD, NSW). The genera Apterobiroina Papp, 1979, Australimosina Papp, 2008, Bentrovata Richards, 1973, Monteithiana Richards, 1973, Popondetta Richards, 1973, and Otwayia Richards, 1973 are treated as new synonyms of Howickia. Howickia is redefined and placed in the context of a key to genera of Sphaeroceridae in Australia, the Australian species of Howickia are keyed, and a morphological phylogeny is given for the Australian species. The following new combinations are given: Howickia australis (Papp, 1979) comb. nov., Howickia cynthia (Richards, 1973) comb. nov., Howickia dealata (Richards, 1973) comb. nov., Howickia flavipes (Papp, 2021) comb. nov., Howickia flaviterga (Richards, 1973) comb. nov., Howickia flavithorax (Papp, 2021) comb. nov., Howickia regalis (Richards, 1973) comb. nov., Howickia sabina (Richards, 1973) comb. nov., Howickia truncata (Papp, 2021) comb. nov., Paralimosina nasalis (Richards, 1973) comb. nov. (formerly in Pseudocollinella Duda, 1924), Pseudopterogramma fenestrata (Richards, 1973) comb. nov. (originally as Leptocera (Limosina) Macquart, 1835, transferred to Biroina Richards, 1973 by Marshall in Roháček et al. (2001)), and Pleuroseta dorrigonis (Richards, 1973) comb. nov. (formerly in Biroina). A new name, Howickia neoregalis nom. nov. is proposed for H. regalis Marshall, 2014, junior homonym of H. regalis (Richards, 1973). The following genera are newly recorded from Australia: Chaetopodella Duda, 1920, Paralimosina Papp, 1973, Pachytarsella Richards, 1963, Parapterogramma Papp, 2008, Philocoprella Richards, 1929, Piliterga Papp, 2008, Pterogrammoides Papp, 1972, Spelobia Spuler, 1924, and Spinilimosina Roháček, 1983.